\(\frac{1}{6}\) - \(\frac{1}{2}\)x = \(\frac{-5}{3}\)
giúp mình nhá!!! ai nhanh mình tik cho!!!
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{1}{3}\) + \(\frac{5}{6}\): \(\left(x-2\frac{1}{5}\right)\)= \(\frac{3}{4}\)
<=> \(\frac{5}{6}\):\(\left(x-2\frac{1}{5}\right)\)= \(\frac{3}{4}\)- \(\frac{1}{3}\)
<=> \(\frac{5}{6}\) : \(\left(x-2\frac{1}{5}\right)\) = \(\frac{5}{12}\)
<=> \(\left(x-2\frac{1}{5}\right)\) = \(\frac{5}{6}\) : \(\frac{5}{12}\)
,<=> \(\left(x-2\frac{1}{5}\right)\)= 2
<=. x = 2 + \(\frac{11}{5}\)
<=> x = \(\frac{21}{5}\)
\(\frac{x+\frac{1}{3}}{1-x^2}+\frac{5}{3x-3}+\frac{1}{3x+3}=\frac{-\left(x+\frac{1}{3}\right)}{x^2-1}+\frac{5}{3.\left(x-1\right)}+\frac{1}{3.\left(x+1\right)}\)
\(=\frac{-x-\frac{1}{3}}{\left(x-1\right)\left(x+1\right)}+\frac{5}{3.\left(x-1\right)}+\frac{1}{3.\left(x+1\right)}=\frac{-3x-1}{3.\left(x-1\right)\left(x+1\right)}+\frac{5x+5}{3.\left(x-1\right)\left(x+1\right)}+\frac{x-1}{3.\left(x-1\right)\left(x+1\right)}\)
\(=\frac{-3x-1+5x+5+x-1}{3.\left(x-1\right)\left(x+1\right)}=\frac{3x+3}{3.\left(x-1\right)\left(x+1\right)}=\frac{3.\left(x+1\right)}{3.\left(x-1\right)\left(x+1\right)}=\frac{1}{x-1}\)
\(-4\frac{1}{3}.\left(\frac{1}{2}-\frac{1}{6}\right)\le x\le-\frac{2}{3}.\left(\frac{1}{3}-\frac{1}{2}-\frac{3}{4}\right)\)
\(\Rightarrow-\frac{13}{3}.\left(\frac{3}{6}-\frac{1}{6}\right)\le x\le-\frac{2}{3}.\left(\frac{4}{12}-\frac{6}{12}-\frac{9}{12}\right)\)
\(\Rightarrow-\frac{13}{3}.\frac{2}{6}\le x\le-\frac{2}{3}.\frac{-11}{12}\)
\(\Rightarrow\frac{-13}{9}\le x\le\frac{11}{18}\)
\(\Rightarrow\frac{-26}{18}\le x\le\frac{11}{18}\)
=> -1,44444444444........... ≤ x ≤ 0,6111111111...........
Mà x ∈ Z
=> x ∈ { -1 ; 0 }
x =(1/6- -5/3] : 1/2
x =11/6 : 1/2
x = 11/3
1/6 - 1/2 .x bằng -5/3
1/2.x bằng 1/6 - -5/3
1/2.x bằng 11/6
x bằng 11/6 : 1/2
x bằng 11/3